Development of A Standardized Scale to Assess Marketing Effectiveness of Farmer-Producer Organisations (FPOs) - HARIHARA TRIPATHY; GOPIKA SOMANATH; Allan Thomas; Smitha S (Indian Journal of Extension Education, 2026)
The study was undertaken to develop a standardised instrument capable of accurately assessing the marketing effectiveness of Farmer-Producer Organisations (FPOs) through the summated rating technique. Initially, 18 dimensions were identified through literature review and expert consultation. Nine dimensions were chosen based on an Item–Content Validity Index of ≥ 0.80. Based on a comprehensive review of literature and consultations with stakeholders of FPOs, 156 statements related to marketing effectiveness were identified. Following extensive editing, 112 statements were selected, out of which 82 statements with relevancy scores greater than 0.85 were retained. Based on the t-test results, 48 statistically significant statements (t > 2.145, p < 0.05) were retained for scale development. A nine-dimensional structure with factor loadings greater than 0.60 was verified by exploratory factor analysis. With a strong split-half reliability coefficient (0.941) and Cronbach’s alpha (0.944), the completed instrument demonstrated excellent reliability. The instrument exhibited strong convergent validity, as evidenced by a high overall Average Variance Extracted of 0.864 and an excellent Composite Reliability value of 0.996. The final 48 items were grouped under nine dimensions. For positive items, scores ranged from 5 (Strongly Agree) to 1 (Strongly Disagree), whereas negative items were evaluated using reverse scoring.